Photospheric Swirls in a Quiet-Sun Region - Quan Xie; Jiajia Liu; Chris J. Nelson; Robert Erdélyi; Yuming Wang (The Astrophysical Journal)
Swirl-shaped flow structures have been observed throughout the solar atmosphere, in both emission and absorption, at different altitudes and locations, and are believed to be associated with magnetic structures. However, the distribution patterns of such swirls, especially their spatial positions, remain unclear. Using the Automated Swirl Detection Algorithm, we identified swirls from the high-resolution photospheric observations, centered on Fe i 630.25 nm, of a quiet region near the Sun's central meridian by the Swedish 1-m Solar Telescope. Via a detailed study of the locations of the detected small-scale swirls with an average radius of  ~300 km, we found that most of them are located in lanes between mesogranules (which have an average diameter of  ~5.4 Mm) instead of the commonly believed intergranular lanes. The squared rotation, expansion/contraction and vector speeds, and proxy kinetic energy are all found to follow Gaussian distributions. Their rotation speed, expansion/contraction speed, and circulation are positively correlated with their radius. All these results suggest that photospheric swirls at different scales and locations across the observational 56 $\mathop{.}\limits^{\unicode{x02033}}$ 5 × 57 $\mathop{.}\limits^{\unicode{x02033}}$ 5 field of view could share the same triggering mechanism at preferred spatial and energy scales. A comparison with our previous work suggests that the number of photospheric swirls is positively correlated with the number of local magnetic concentrations, stressing again the close relation between swirls and local magnetic concentrations: the number of swirls should positively correlate with the number and strength of local magnetic concentrations.